Answer:
for quadratic equation 1
y^2-10y+21=0
Step-by-step explanation:
y^2-7y-3y+21=0
y(y-7)-3(y-7)=0
(y-7)(y-3)=0
y-7=0,y-3=0
y=7,y=3
y=(3,7)
for quadratic equation 2
16p^2-8p+1=0
16p^2-4p-4p+1=0
4p(4p-1)-1(4p-1)=0
(4p-1)twice=0
4p-1=0,4p-1=0
4p=1
p=1/4 twice
for quadratic equation 3
x^2-400=0
x^2=400
x=√400
x=20
for quadratic equation 4
-16m^2-8m-1=0
multiply the equation by -
16m^2+8m+1=0
16m^2+4m+4m+1=0
4m(4m+1)1(4m+1)=0
4m+1=0 twice
m=-1/4 twice
for quadratic equation 5
-3n^2+75=0
divide both side by -3
-3n^2/-3=-75/-3
n^2=25
n=√25
n=5
To solve a problem like this, we need to start with the innermost parenthesis. Doing that, we get to 4+1, evaluating it giving us 5. This turns our expression into 5 x {3 x [9 - 5]} + 20 ÷ 4 x 2.
Now, the innermost parenthesis is 9-5. Evaluating that gives us 4. Our expression is now 5 x {3 x 4} + 20 ÷ 4 x 2.
Once again, we go to the innermost parenthesis and evaluate whatever is there. This turns our expression into <span>5 x 12 + 20 ÷ 4 x 2.
Now, we can simply use order of operations to compute that the value of the expression is equal to 70. </span>